1987
DOI: 10.1520/jfs12402j
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated Morphine in Blood by Radioimmunoassay and Gas Chromatography/Mass Spectrometry

Abstract: Morphine, the active metabolite of heroin, is rapidly inactivated by glucuronidation at the 3 carbon. Unconjugated (pharmacologically active) morphine was measured in postmortem blood by radioimmunoassay using an antibody-coated tube kit. The kit shows less than 0.2% cross-reactivity with codeine and morphine-glucuronide. Unconjugated morphine concentrations were confirmed by gas chromatography/mass spectrometry (GC/MS) using deuterated morphine as the internal standard. The blood was precipitated with 10% tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Furthermore, this ratio was always greater than 50%, which from consideration of the pharmacokinetics [2] indicates a rapid death in less than three hours. It is also interesting to note that in 30 of these 44 cases (68.2%), the drug material was found near the body.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, this ratio was always greater than 50%, which from consideration of the pharmacokinetics [2] indicates a rapid death in less than three hours. It is also interesting to note that in 30 of these 44 cases (68.2%), the drug material was found near the body.…”
Section: Resultsmentioning
confidence: 93%
“…Spiehler and Brown [2] have recently shown that the ratio of free to total morphine in blood could be used to estimate the time elapsed since the injection of heroin.…”
Section: Introductionmentioning
confidence: 99%
“…1 Codeine is metabolized by several mechanisms (discussed below), and the metabolites can be analyzed either as the total (the combined free drug plus the hydrolyzed conjugates) or the free drug alone. The difference between the total and free drug concentrations equals the amount of conjugated drug.…”
Section: Autopsy and Toxicology Resultsmentioning
confidence: 99%
“…below or similar to those of living consumers or intoxicated heroin users [3,7]. Some authors have studied the ratio of "free" to "total" morphine, in order to correlate this value with the time of death or the influence of other misused drugs [11][12][13]. "Free" morphine stands for un-conjugated morphine, while "total" morphine refers to the amount of morphine which is determined after application of a hydrolysis step to the sample.…”
Section: Introductionmentioning
confidence: 99%